2013
DOI: 10.1186/1752-1947-7-35
|View full text |Cite
|
Sign up to set email alerts
|

Vascular-type Ehlers-Danlos syndrome caused by a hitherto unknown genetic mutation: a case report

Abstract: IntroductionVascular-type Ehlers-Danlos syndrome is an autosomal dominant disease that causes arterial spurting, intestinal perforation, uterine rupture and hemopneumothorax due to decreased production of type III collagen. The average age at death is 48 years old, and it is considered to be the most severe form of Ehlers-Danlos syndrome. We report the case of a 64-year-old Japanese woman and her 38-year-old daughter who were diagnosed with this disease.Case presentationA 64-year-old Japanese woman was referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Table summarizes the design and publication date characteristics of the 105 included studies . Studies consisted of case reports/series (N = 62, 60%) and observational studies (N = 43, 40%), including cross sectional (N = 29), case‐controlled (N = 12), and cohort (N = 2) designs.…”
Section: Resultsmentioning
confidence: 99%
“…Table summarizes the design and publication date characteristics of the 105 included studies . Studies consisted of case reports/series (N = 62, 60%) and observational studies (N = 43, 40%), including cross sectional (N = 29), case‐controlled (N = 12), and cohort (N = 2) designs.…”
Section: Resultsmentioning
confidence: 99%
“…The body of literature regarding pulmonary complications in vEDS consists of case reports (Abrahamsen, Kulseth, & Paus, ; Dar, Wani, Mushtaque, & Kasana, ; Gu et al, ; Ishiguro et al, ; Kashizaki, Hatamochi, Kamiya, Yoshizu, & Okamoto, ; Omori et al, ; Sadakata et al, ; Selim, Lane, Rubinowitz, & Siner, ). The majority of these case reports include males with an average age of 24 years (range 11–64) at presentation, not unlike the mean age of initial P/HTX presentation in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…144,145 Four major (skin hyperextesibility, widened atrophic scarring, joint hypermobility, and positive family history) and minor diagnostic criteria have been identified to clinically establish the EDS diagnosis. 145,146 Six major types of EDS have been classified, classic (type 1 and 2), hypermobility (type 3), vascular (type 4), kyphoscoliosis (type 6), arthrochalasia (type 7A-B), and dermatosparaxis (type 7C). 144,145 The classification is based on the clinical and corresponding molecular pathogenetic findings in collagen types I, III, and V, or processing enzymes, with the category clinical descriptor capturing the pathognomonic manifestation of each type.…”
Section: Authors' Commentmentioning
confidence: 99%
“…Lungs can be affected by EDS, and most cases are of the vascular type. Vascular type or type 4 EDS is caused by mutations of type III collagen (COL3A1) gene, 146 and is considered a clinically dramatic form because of blood vessel fragility. Experimental studies have demonstrated the extreme sensitivity of Col3a1-insufficient mice to prematurely develop thoracic aortic ruptures in response to angiotensin II and its associated high levels in high blood pressure conditions.…”
Section: Authors' Commentmentioning
confidence: 99%